Youth in the Countryside and in the City – Job Quality and the Diversity of Employment Opportunities for Young People - Jelonek, Magdalena (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The article examines the differences in the quality of employment available to young people living in rural areas and cities. It argues that the latter are more likely to not only have a job, but also one of high quality. In the article, job quality is characterised using the OECD’s three dimensions: the level of remuneration, employment stability and the quality of the work environment. The survey data collected as part of Human Capital in Poland (BKL) was used to verify the assumptions. The study makes two main contributions to the literature. First, it shows that the greatest differences between urban and rural residents are associated with the superior opportunity urban dwellers have for economic advancement. Second, it identifies two key factors that moderate the relationship between place of residence and quality of employment: 1) the region (strong or weak urban centers) and 2) the level of education (higher or lower levels).